BAHASA KEI DALAM KOMUNIKASI INTERPERSONAL PEMUDA DI OHOI OHOIJANG KECAMATAN KEI KECIL KABUPATEN MALUKU TENGGARA - FERONIKA NARWADAN; DAMIANUS FOFID (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
This study discusses Kei Language in Youth Interpersonal Communication in Ohoi Ohoijang, Kei Kecil District,Southeast Maluku Regency. Language is a cultural tool used by humans to communicate or relate to each other, eitherthrough written, oral, or movement. Kei language is the regional language used by the Kei tribe. Along with thedevelopment of the increasingly advanced globalization era, the importance of preserving the Kei language. In fact,currently Kei youth, can no longer communicate using the natural Kei language to do interpersonal communication.This phenomenon raises concerns that when Kei youths cannot understand or communicate in Kei language, thecustoms and traditions of the Kei Islands will disappear. For example, during customary meetings, and traditionalrituals that require a person to communicate intrapersonal using Kei language. It is feared that in the future the Keilanguage will become extinct by itself. Thus, it is necessary to know how the interpersonal communication of Keilanguage itself and the factors that cause Kei language to no longer be used by youth in everyday life. This type ofresearch is qualitative by using primary data sourced from field research data, and secondary data throughinformants. The results showed that Ohoi Ohoijang youth did not use Kei in their daily interactions, youth were morelikely to use Indonesian or slang to interact. Lack of recognition of the Kei language by parents.